Methamphetamine-Related Psychiatric Symptoms with Special Reference to COVID-19 Issues - Valerie Yarema MSW; David Wellisch (Journal of Addiction Medicine and Therapeutic Science - Peertechz Publications, 2020)
This short form review article summarizes the psychiatric symptoms associated with methamphetamine use including psychosis and places a special focus on the intersection of methamphetamine use and the COVID-19 pandemic.